1998
DOI: 10.1109/42.712138
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocardiographic localization of arrhythmia substrates: a methodology study with accessory pathway ablation as reference

Abstract: In magnetocardiographic (MCG) localization of arrhythmia substrates, a model of the thorax as volume conductor is a crucial component of the calculations. In this study, we investigated different models of the thorax, to determine the most suitable to use in the computations. Our methods and results are as follows. We studied 11 patients with overt Wolff-Parkinson-White syndrome, scheduled for catheter ablation. The MCG registrations were made with a 37-channel "superconducting quantum interference device" sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…It is of importance to better understand the mechanisms of cardiac physiology and pathophysiology and further to develop clinically applicable, noninvasive cardiac mapping techniques. A number of efforts have been put forth in the past decades in the development of the noninvasive cardiac electrical imaging techniques to estimate the equivalent cardiac source inversely from body surface potential mappings (BSPMs, Gulrajani et al 1984a, Burnes et al 2000, He and Wu 1997, 2001, Li and He 2001, Tilg et al 2002, Zhang et al 2005), magnetocardiographic (MCG, Agren et al 1998, Leder et al 1998a, Fenicir 2003) field mappings, or directly by comparing the BSPMs (SippensGroenewegen et al . 1990, Green et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is of importance to better understand the mechanisms of cardiac physiology and pathophysiology and further to develop clinically applicable, noninvasive cardiac mapping techniques. A number of efforts have been put forth in the past decades in the development of the noninvasive cardiac electrical imaging techniques to estimate the equivalent cardiac source inversely from body surface potential mappings (BSPMs, Gulrajani et al 1984a, Burnes et al 2000, He and Wu 1997, 2001, Li and He 2001, Tilg et al 2002, Zhang et al 2005), magnetocardiographic (MCG, Agren et al 1998, Leder et al 1998a, Fenicir 2003) field mappings, or directly by comparing the BSPMs (SippensGroenewegen et al . 1990, Green et al .…”
Section: Introductionmentioning
confidence: 99%
“…The MCG has been used predominantly in Europe since the 1970s [2]. Most studies were done to localize arrhythmias in conditions with ventricular pre-excitation, Wolf-Parkinson-White and accessory pathways, and more recently atrial fibrillation [3,4,5,6,7,8,9,10,11]. The sensitivity and capability of the MCG for the detection of ischemia has been evaluated in only a few small clinical studies [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage is that the data in MCGs are vector markers using absolute scales, whereas the data in ECGs are scalar markers using relative scales. These advantages have been explored in MCG studies of Wolff-ParkinsonWhite syndrome, 7,8 and ischemic heart disease. 9,10 The accuracy of MCGs is affected by the distance between the magnetic source and the SQUID sensor, by body motion associated with respiration and the heartbeat, and by the models used to analyze the data.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The accuracy of MCGs is affected by the distance between the magnetic source and the SQUID sensor, by body motion associated with respiration and the heartbeat, and by the models used to analyze the data. 8 The sampling data is therefore usually signal-averaged, but this is inapplicable to Af, atrial flutter and atrial tachycardia because they are complicated arrhythmias with irregular atrioventricular conduction. We have already reported that MCGs can distinguish atrial flutter caused by macro reentry from atrial tachycardia caused by other mechanisms (automaticity or micro reentry), 4 and in the present study we have developed a new algorithm for analyzing atrial activation in patients with AS and Af 6 by using QRS-T subtraction and timefrequency analysis.…”
Section: Discussionmentioning
confidence: 99%